Preparation of corn (Zea mays) and sorghum (Sorghum bicolor) proteins and protein hydrolysates and their antihypertensive activities - Núñez C., Luis F. (Zamorano: Escuela Agrícola Panamericana, 2019., 2019)
The most important group of protein in cereals is prolamine, storage protein in cereal grains that contain biopeptides, which can prevent non-transmissible diseases such as hypertension. The objective of the present study was to determine the composition of sorghum, white and yellow corn proteins, as well as to prepare protein hydrolysates in order to evaluate their antihypertensive activities. Protein extraction using the alkaline method in combination with combined ultrasound reached 65.7, 63.5 and 48.1% for white corn, yellow corn and white sorghum, respectively. A comparison was made between corn and sorghum proteins; it was found that there are no significant differences between treatments (P > 0.05), because with the concentration of 1% of protein incubated for 3 hours reached approximately 24% of degree of hydrolysis. However, the hydrolysis time obtained a significant difference (P < 0.05) until reaching a saturation point at 60 minutes and 90 minutes for sorghum and corn, respectively. Corn and sorghum proteins, and their hydrolysates at the point of saturation, were subjected to the angiotensin-converting enzyme inhibition test. The best treatments obtained results of 45.4 and 43.8%, for yellow corn and white corn, respectively. The least effective treatment was white sorghum with 30.5%. It is recommended to use purification and separation methods to differentiate the biopeptides released during hydrolysis.